ANALISIS PRODUKSI SAYURAN DALAM RANGKA PEMENUHAN KONSUMSI SAYURAN DI KOTA PEKANBARU PROVINSI RIAU - Elinur Djaimi (Universitas Negeri Medan, 2016)
Demand vegetables in the city of Pekanbaru increased, but relatively similar vegetable production and a tendency to decline. This study aimed to analyze the dominant factors that determine the production of vegetables and return to scale of vegetables in Pekanbaru. Sampling metode was multi-stage random sampling with a sample of 44 vegetable farmers. The production function used is function cobb douglas with the estimation method Ordinary Least Square (OLS). Results of this researh revealed that, first: The dominant factor affecting vegetable production is labor, seed and fertilizer urea at 5 percent level of convidence and determination coefficient of 93.40 percent. Second, return to scale of vegetable farming was Decreasing Return to Scala (DRTS). This means that if the factorsof production increased by 1 percent, the production of vegetables will increase by 0.985 percent. Third, the policy implications that must be done by the government in order to meet the demand of vegetables for the city of Pekanbaru made efforts to increase intensification.